2016
DOI: 10.1016/j.jiph.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering emerging Zika and dengue viral epidemics: Implications for global maternal–child health burden

Abstract: Since its discovery in 1947 in Uganda and control and eradication efforts have aimed at its vectors (Aedes mosquitoes) in Latin America in the 1950s, an absolute neglect of Zika programs and interventions has been documented in Aedes endemic and epidemic-prone countries. The current unprecedented Zika viral epidemics and rapid spread in the Western hemisphere pose a substantial global threat, with associated anxiety and consequences. The lack of safe and effective drugs and vaccines against Zika or dengue epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…The importance of implementing a local and national "One Health" policy and programs holds tremendous prospects, such as co-tackling the epidemiological and environmental challenges, and accelerating in the transition from control to elimination of infectious diseases under China-Africa collaboration [5,15]. Furthermore, it has potential to revolutionize national health systems, policies and strategic priorities and the patterns in health financing and resources allocation of African countries that require careful understanding of the local context of diverse stressors and drivers [21,13]. These will continue to dominate the performance and effectiveness of "One Health" in threats and epidemics prevention strategies and policies on healthcare and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of implementing a local and national "One Health" policy and programs holds tremendous prospects, such as co-tackling the epidemiological and environmental challenges, and accelerating in the transition from control to elimination of infectious diseases under China-Africa collaboration [5,15]. Furthermore, it has potential to revolutionize national health systems, policies and strategic priorities and the patterns in health financing and resources allocation of African countries that require careful understanding of the local context of diverse stressors and drivers [21,13]. These will continue to dominate the performance and effectiveness of "One Health" in threats and epidemics prevention strategies and policies on healthcare and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the climate change, global migration and country-specific complexities of emerging and current infectious diseases of poverty is needed in tackle operational programs challenges and bottlenecks, improved sustained control into elimination. For example national immunization programs hesitancy and resistance issues, such as misconceptions and mistrust or fear, weak coverage and non-adherence, persistent resurgence of zoonotic threats and emerging epidemics, continue to place a huge toll of maternal and child health morbidity and mortality on burden and coupled with the rising trend of chronic diseases related inequities and poverty vicious cycle [8,9,10,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the dreadful epidemics impact on health and economic requires innovative capabilities to support health systems and frontline workforce, in fostering continuous risk communication and awareness for timely decision making policies, readiness and rapid response interventions strategies improvements and frontline such as enhanced ICT-based and social media applications benefits [2,7,17]. Real time, comprehensive and reliable access to and advocacy for use of Zika virus epidemics data and information can be very timely in risk identification, magnitude of transmission and spread within and between populations, early community alertness and awareness, risk communication, prognosis and early warning, social mobilization and community engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in strengthening Aedes mosquito and great-apes and treatment care delivery or effective response strategy in these recent epidemics through various IT applications [6,18]. For example Zika epidemics-related Twitter incidence showed that User-generated contents sites were preferred direct information channels rather than those of the government authorities including societal impact of the outbreak; government, public and private sector, and general public responses to the outbreak; pregnancy negative health consequences related to pregnant women and babies outcomes, microcephaly and neurological syndrome; transmission routes; and new case reports [3,5,9,17]. A recent published paper on Zika epidemics have shown that the public showed more concern about the complications or consequences it had for women and babies, whereas WHO and CDC increased Zika epidemics guidelines and precautionary measures for women at child bearing information, awareness and active education.…”
Section: Introductionmentioning
confidence: 99%
“…Zika population-based operational research on longitudinal cohorts on direct and indirect transmission linked pregnant women and affected families' mental and psychosocial services analysis should be fully resourced to understand and establish improved integrated vector management (IVM), sexual and reproductive interventions and measures. Strengthening Zika routine health system surveillance-response systems and research programs/projects is critical in prevention and control of pregnancy outcomes in prone settings and territories [6,9,10]. In addition, elucidating Aedes and sexual transmission related Zika virus transmission ecological, adaptation and human health threat and complications requires coordinated approach to data sharing, surveillance and research is needed in defining the full spectrum of congenital Zika virus syndrome and issues on maternal-child health [11][12][13].…”
mentioning
confidence: 99%